VD_FINDINFO Jug / 2021 / 237 vom 29. September 2020 - VD Tribunal cantonal (2020)
DROIT D'ÊTRE ENTENDU, CONSTATATION DES FAITS, APPRÉCIATION DES PREUVES | 10 CPP (CH), 139 CPP (CH), 343 CPP (CH), 350 CPP (CH), 389 CPP (CH)